Studies in Ancient Israelite Wisdom: Selected with a Prolegomenon (1976)
$25.00; 27 Beiträge, u.a. F. С. Fensham, Widow, Orphan and the Poor in Ancient Near Eastern Legal and Wisdom Literature; R. B. Y. Scott, Folk Proverbs of the Ancient Near East.